The articulation of the past and the ethical key of testimony in “Caderno de memórias coloniais”, by Isabela Figueiredo - Cavelagna, Rodrigo (2021)
Caderno de memórias coloniais, by Isabela Figueiredo (2018), is composed of a memoirist writing, in which a narrator-character remembers her childhood, covering the period of the Mozambican War of Independence (1964-1974) and, subsequently, the process of social and political change that takes place in Portugal after April 25, 1974. The book represents the oppression of the colonial regime and the denunciation of its violence, using various aesthetic resources, with a fragmentary composition that translates the complexity of the inscribed testimony. In this article, we will focus in the reflections on memory, on the resumption of themes by Levi (2016), and in the elaboration of the testimony, from the ethical-political posture assumed by the narrator-character.For this discussion, we will use specific analyses, in Silvio Jorge (2015) and Daniel Laks (2019), and general bibliography, in Walter Benjamin (2012), Márcio Seligman-Silva (2008) and Jeanne Marie Gagnebin (2009).